The Effect of Sharia Compliance and Islamic Corporate Governance on Financial Performance in Islamic Commercial Banks in Indonesia for the 2016-2021 Period - Khairunnisa Putri Nabila; Hendra Harmain; Kusmilawaty . (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
This research uses a quantitative approach. The variable data type is secondary data, namely data obtained from the annual report published on the official website of each bank for the 2016-2021 period. The data analysis techniques used in this study include Descriptive Statistical Analysis, Classical Assumption Test consisting of Normality Test, Multicholinearity Test, Autocorrelation Test, and Heteroskedasticity Test, Hypothesis Test consisting of t Test, F Test, Coefficient of Determination, and Multiple Linear Regression Test with the help of the Eviews 10 application. The results of this study show that partially (t test) sharia compliance with islamic income ratio (IsIR) indicators has a positive and significant effect on financial performance. Partial sharia compliance with the profit sharing ratio (PSR) indicator has a positive and significant effect on financial performance. Partial sharia compliance with the Islamic investment ratio (IIR) indicator has a negative and insignificant effect on financial performance. Partial sharia compliance with the zakat performing ratio (ZPR) indicator has a negative and insignificant effect on financial performance. In part, Islamic corporate governance has a positive and significant effect on financial performance. Simultaneously (F test) the variables Islamic income ratio (IsIR), profit sharing ratio (PSR), Islamic investment ratio (IIR), zakat performing ratio (ZPR) and Islamic corporate governance (ICG) have a significant effect on the financial performance of Islamic commercial banks.